How fat works - Wood, Philip A. (Philip Allen) (Harvard University Press, 2006)
How Fat Works is a concise and up-to-date primer on the workings of fat. It is essential reading for professionals entering careers in medicine and public health administration or anyone wanting a better understanding of one of our most urgent health crises.